2015
DOI: 10.1016/j.fsigen.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of common forensic presumptive tests on the ability to obtain results using a novel rapid DNA platform

Abstract: The rise of DNA evidence to the forefront of forensic science has led to high sample numbers being submitted for profiling by investigators to casework laboratories: bottleneck effects are often seen resulting in slow turnaround times and sample backlog. The ParaDNA® Screening and IntelligenceTests have been designed to guide investigators on the viability of potential sources of DNA allowing them to determine which samples should be sent for full DNA analysis. Both tests are designed to augment the arsenal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This could account for the reduced quality of the profiles obtained. Another study demonstrated no effect from presumptive tests on the resulting profile (Donachie et al, ).…”
Section: Direct Pcrmentioning
confidence: 97%
See 1 more Smart Citation
“…This could account for the reduced quality of the profiles obtained. Another study demonstrated no effect from presumptive tests on the resulting profile (Donachie et al, ).…”
Section: Direct Pcrmentioning
confidence: 97%
“…There is some concern over the effect of common presumptive and enhancement tests on direct PCR reactions (Donachie et al, 2015). One study has been completed that showed some negative effects on the resulting profiles, for example, when using the Kastle-Meyer and leucomalachite green tests (Thanakiatkrai, Raham, Pradutkanchana, Sotthibandhu, & Kitpipit, 2017).…”
Section: Effects Of Screening Testsmentioning
confidence: 99%
“…Donachie et al concluded that the ParaDNA system could be used as a presumptive test for samples with medium to high template DNA present, such as blood, saliva, and semen stains. For low template samples, such as touch DNA (e.g., single fingerprints), the success rate was too low [ 43 ].…”
Section: Rapid Dna Systemsmentioning
confidence: 99%
“…The screening test is able to obtain a gender result in >80% of samples with a sufficient presence of DNA (>62.5 pg), though is more sensitive to male samples than female due to software reporting a male result whenever a Y target is amplified [69]. There has also been some assessment of whether the assay interferes with existing forensic processes with research demonstrating that pre-treatment of samples with Phadebas and luminol/Bluestar® did not impact the ability of ParaDNA to reliably screen these samples for DNA [72]. However, despite the ease of use and portability, the ParaDNA screening test is intended to augment the existing processes of sample submission and case management, and not designed to replace existing tools [73] meaning that costs savings may be more difficult to identify.…”
Section: Dna-based -Humanmentioning
confidence: 99%